HUBUNGAN MASA KERJA DENGAN PERILAKU PETUGAS MEDIS DALAM PENANGANAN SAMPAH MEDIS DI RSUD ROKAN HULU TAHUN 2019 - Milda Hastuty (Universitas Pahlawan, 2019)
Medical waste is rubbish originating from outpatient rooms, inpatient rooms, Intensive Care Unit (ICU) rooms, Operating rooms and Emergency Room Installation (IGD) so that the handling process needs attention. The World Health Organization (WHO) states that all people exposed to hazardous waste from health facilities are likely to be at risk, including those in hazardous waste-producing facilities. The purpose of this study was to determine the relationship of work period with the behavior of medical personnel in handling medical waste in Rokan Hulu District General Hospital in 2019. This type of research is analytic with cross sectional design. The population in this study were all medical officers in Rokan Hulu District Hospital, amounting to 390 people with a sample of 198 respondents taken by simple random sampling technique. Data collection tools using a questionnaire and analysis using the Chi-Square test. The results obtained p value of 0.001, which means there is a significant relationship between work time with the behavior of medical officers in handling medical waste. The results of this study are expected to contribute to improving the behavior of medical staff in sorting solid medical waste in hospitals.